2018
DOI: 10.3389/fphys.2018.01250
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vitellogenin and Vitellogenin Receptor of Conopomorpha sinensis Bradley and Their Responses to Sublethal Concentrations of Insecticide

Abstract: Conopomorpha sinensis Bradley is the dominant borer pest of Litchi chinesis and Euphoria longan. Current management of C. sinensis relies upon insecticide application to adult moths. In addition to the direct mortality induced by insecticides, a sublethal dose of insecticides also affects growth, survival, and reproduction in the exposed insects. Vitellogenin (Vg) and vitellogenin receptor (VgR) are normally identified as essential reproduction-related proteins in insects. In this study, we characterized these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 47 publications
5
31
1
Order By: Relevance
“…We cloned and identified the ORF sequences of SfVg and SfVgR from S. furcifera and analyzed the molecular characteristics of these genes. As expected, the amino acid sequence of SfVg contains the LPD_N, VWD and DUF1943 domains, all of which are highly conserved in most insects (Tufail et al, 2010;Wu et al, 2018;Yao et al, 2018). The motifs GL/ICG, DGXR and K/RXXR/K are also regarded as conserved domains in insect Vg proteins (Sappington and Raikhel, 1998;Upadhyay et al, 2016) and we found a GLCG motif at the C-terminal of SfVg.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We cloned and identified the ORF sequences of SfVg and SfVgR from S. furcifera and analyzed the molecular characteristics of these genes. As expected, the amino acid sequence of SfVg contains the LPD_N, VWD and DUF1943 domains, all of which are highly conserved in most insects (Tufail et al, 2010;Wu et al, 2018;Yao et al, 2018). The motifs GL/ICG, DGXR and K/RXXR/K are also regarded as conserved domains in insect Vg proteins (Sappington and Raikhel, 1998;Upadhyay et al, 2016) and we found a GLCG motif at the C-terminal of SfVg.…”
Section: Discussionsupporting
confidence: 85%
“…VgR belongs to the low-density lipoprotein receptor (LDLR) family (Tufail and Takeda, 2009;Zhao et al, 2018). The amino acid sequences of VgR include five highly conserved and functionally different amino acids domains; a ligand binding domain (LBD), an epidermal growth factorprecursor domain (EGF), an O-linked sugar domain, low-density lipoprotein-receptor Tyr-Trp-Thr-Asp (YWTD) repeats and a transmembrane domain (Sappington and Raikhel, 1998;Tufail and Takeda, 2009;Shang et al, 2018;Yao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Chilo suppressalis , the sublethal concentration of chlorantraniliprole significantly inhibited CsVg expression ( Huang et al 2016 ). In Conopomorpha sinensis , the sublethal concentration of emamectin benzoate significantly inhibited Vg expression ( Yao et al 2018 ). Overall, these results indicate that insecticides affect insect reproduction via stimulation or inhibition by regulating Vg gene expression and synthesis and its transfer to the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…Reproduction is one of the most important physiological behaviors of insects, which is also the basis for the population growth. Further investigations on the processes of reproduction and underlying mechanisms of the injurious insects could reveal potential molecular targets for the prevention of the insects, which are current research hotspots across the world (Roy et al 2018; Shang et al 2018; Yao et al 2018; Zhao et al 2018; Liu et al 2019).…”
mentioning
confidence: 99%
“…Vitellogenin receptor is the exclusive receptor for endocytosis of vitellogenesis, which has a critical role in the uptake of vitellogenesis (Tufail and Takeda 2009). Previous studies have shown that when the expression of VgR gene is abnormal, the deposition of vitellin in oocytes is disrupted, which in turn delays the development of ovary and can even lead to female sterility (Lu et al 2015; Upadhyay et al 2016; Shang et al 2018; Yao et al 2018).…”
mentioning
confidence: 99%